Performance Analysis of Costs and Implementation Time Using Earned Value Method on the Distribution Pipe Network Expansion in Samarinda City - Hartawan, Dedy Sugi; Oetomo, Wateno; Marleno, Risma (LPPM of NAROTAMA UNIVERSITY, 2024)
The problems raised in this research relate to the implementation performance of the Samarinda City distribution piping network expansion project. With the increasing need for clean water and the increasing population, PDAM Kota Samarinda must be able to meet demand with quality, quantity, continuity and accessible prices, as well as adequate water pressure. In an effort to provide clean water services, the government must pay special attention to developing the distribution network. The previous distribution piping network in Samarinda City is considered to need to be expanded to meet the need for clean water, especially during the dry season where there is a shortage of clean water in the Samarinda area. Based on the background of this problem, the title of this research is Analysis of cost performance and implementation time using the EVM Method (Earned Value Method) in the Samarinda City Distribution Pipeline Network Expansion Work. This research was carried out with the aim of determining the cost and time for completing the project. The research method uses calculation and analysis of ACWP, BCWP, BCWS, Cost Performance Index, Cost Variance, Earned Value, Earned Value Method, EVM, Schedule Variance, Variance at Completion. Based on the analysis of the data obtained, it can be concluded that the cost performance is not in accordance with the budget and the estimated cost until the project is completed is IDR. 20,583,636,709, greater than the planned Rp. 16,566,678,000. Time performance in weeks 4 to 20 experienced delays. Estimated project completion time is 163 days or 24 weeks. longer than planned, namely 161 days.